The impact of drinking brewed coffee on VO2max and blood lactate levels in sedentary males with physical activity treatment - Shidqi, Muhammad; Idayati, Ratna; Yusni, Yusni (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: Coffee is a popular ergogenic beverage that improves stamina and reduces fatigue. Coffee's caffeine content is thought to be the main ingredient in ergogenic supplements, which increase endurance during physical activity.Objective: This study investigates the acute effect of brewed coffee on muscle fatigue markers, namely blood lactate and volume of oxygen maximum (VO2max), in sedentary males after a standardized physical activity protocol.Methods: This research was quasi-experimental (posttest-only with a control group design). The subjects were men aged 18-22 years, with 16 people. They were divided into a control group (n=9) and a intervention group (n=7). The intervention was heavy physical activity (1600-meter run) and Gayo Arabica coffee. Data analysis used an independent sample t-test (p < 0.05).Results: Blood lactate levels were significantly higher in the intervention group than in the control group (15.04 ± 2.38 vs. 10.60 ± 4.10; p = 0.018), even though VO2max values were higher but not statistically significant (39.57 ± 2.37 vs. 37.62 ± 4.17; p = 0.297).Conclusions: Coffee consumption considerably raises blood lactate levels, but it has no discernible effect on VO2max values in sedentary men who exercise vigorously. Therefore, more research is necessary to fully understand how coffee affects ergogenic and fatigue.Keywords: Coffee; VO2max; blood lactate; sedentary; heavy physical activity